Pengaruh Kebijakan Perpustakaan terhadap Akses Informasi : Studi Bibliometrik - Muhaemin Muhaemin (Perpustakaan Nasional, 2024)
This study aims to analyze and map bibliometrically the results of research in the Dimensions database on the effect of library policy on inclusive, fair and quality information access for the community. The method used is a bibliometric study by analyzing 125 research sources from the Dimensions database in the 2014-2023 time span. The analysis was conducted using Biblioshiny to map authors, sources, countries and dominant keywords. There are three categories of information access, namely Open access, Close access, and Closed and open access. The countries that published the most research were the United States and South Africa. Some of the dominant keywords are public libraries and academic libraries. The results of this study show that library policies have an influence in providing access to information for the public. There are challenges in implementing policies that support equal access, especially for minority groups and people with disabilities. This research trend focuses on public and academic libraries as the frontline in providing access to information for people from all walks of life. In conclusion, this research emphasizes the importance of developing dynamic and responsive library policies to address structural inequalities, improve accessibility and bridge the digital divide in accessing information.